KARAKTERISTIK FISIKOKIMIA DAN SENSORI MI ANALOG BERBASIS SINGKONG DENGAN PENAMBAHAN KARAGENAN [PHYSICOCHEMICAL AND SENSORY CHARACTERISTICS OF CASSAVA BASED NOODLE ANALOGUE WITH CARRAGEENAN ADDITION] - Hardoko Hardoko; Delicia Martha; Yuniwaty Halim (FaST - Jurnal Sains dan Teknologi (Journal of Science and Technology), 2021)
Cassava noodles are considered as a type of non-gluten-based noodles that have stickiness and higher cooking loss than wheat noodles. The addition of several types of hydrocolloids was allegedly able to improve the quality of starch-based analog noodles. The purpose of this study was to determine the characteristics of analogue noodles based on cassava plus carrageenan hydrocolloid compared to wheat noodles. The research method used was the experimental method of adding 0%, 5%, 10%, and 15% carrageenan to the cassava-based analog noodle formulation. The results showed that the addition of carrageenan to cassava-based analog noodles reduced the elasticity, chewability, water absorption and elongation of noodles, but increased the stickiness, tensile strength, and elasticity of analog noodles. Analog noodles whose characteristics of elasticity, stickiness, and hardness are close to that of commercial wheat noodles are those with 10% carrageenan added. The level of preference for cassava-based analog noodles added with 10% carrageenan was still below commercial wheat noodles which reached a hedonic level of moderate liking (score 5.0), however, the level of preference for analog noodles still reached neutral to moderate (4.5-5.0).BAHASA INDONESIA ABSTRAK: Mie singkong dianggap sebagai jenis mie berbasis non-gluten yang  memiliki sifat lengket dan susut masak lebih tinggi daripada mi terigu. Penambahan beberapa jenis hidrokoloid disinyalir dapat memperbaiki mutu mi analog berbasis pati. Tujuan dari penelitian ini adalah untuk mengetahui karakteristrik mi analog berbasis singkong  yang ditambah hidrokoloid karagenan dibandingkan dengan mi terigu. Metode penelitian yang digunakan adalah metode eksperimen penambahan karaginan 0%, 5%, 10%, dan 15% pada formulasi mi analog berbasis singkong. Hasil penelitian menunjukkan bahwa Penambahan karagenan pada mi analog berbasis singkong dapat menurunkan kekenyalan, daya kunyah, daya serap air, dan elongasi mi, tetapi menaikkan kelengketan, kuat tarik, dan elastisitas mi analog. Mi analog yang karakteristik kekenyalan, kelengketan, dan kekerasan nya mendekatai mi terigu komersiil adalah yang ditambah karagenan 10%. Tingkat kesukaan terhadap mi analog berbasis singkong yang ditambah karagenan 10% masih dibawah mi terigu komersiil yang mencapai tingkat hedonik agak suka (skor 5,0), meskipun demikian tingkat kesukaan mi analog masih mencapai netral sampai agak suka (4,5-5,0).